2019
DOI: 10.1038/s41372-019-0556-x
|View full text |Cite
|
Sign up to set email alerts
|

Early oral colostrum administration in preterm infants

Abstract: Background Early administration of colostrum may provide preterm infants with immune components. Previous studies illustrating the effects of oral colostrum (OC) have been confounded by the coincidence of enteral feedings. Objective To quantify OC absorption, as measured by urinary sIgA and lactoferrin, in preterm infants prior to enteral feedings. Materials and methods Colostrum was obtained from mothers delivering infants ≤32 weeks and ≤1500 g. sIgA and lactoferrin were measured in infant urine, and microflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
1
21
0
3
Order By: Relevance
“…Additionally, there is evidence for better developmental outcomes of premature infants when fed with their own mothers' milk compared to the mismatched milk of an anonymous donor (eg, De Halleux et al, 2019; Heiman & Schanler, 2006; Montjaux‐Régis et al, 2011). The oral administration of the mother's colostrum to preterm neonates additionally canalizes their oral microbiota and immunity (Glass, Greecher, & Doheny, 2017; Maffei, Brewer, Codipilly, Weinberger, & Schanler, 2020; Snyder et al, 2017), but it may also subject them to chemosensory incentives. Finally, suffusing own mother's milk odor into the incubator quasi‐continuously for 3 days promotes the psychophysiological stabilization of preterm infants (Park & Im, 2020), further suggesting sustained adaptive effects of the odor of age‐matched milk.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is evidence for better developmental outcomes of premature infants when fed with their own mothers' milk compared to the mismatched milk of an anonymous donor (eg, De Halleux et al, 2019; Heiman & Schanler, 2006; Montjaux‐Régis et al, 2011). The oral administration of the mother's colostrum to preterm neonates additionally canalizes their oral microbiota and immunity (Glass, Greecher, & Doheny, 2017; Maffei, Brewer, Codipilly, Weinberger, & Schanler, 2020; Snyder et al, 2017), but it may also subject them to chemosensory incentives. Finally, suffusing own mother's milk odor into the incubator quasi‐continuously for 3 days promotes the psychophysiological stabilization of preterm infants (Park & Im, 2020), further suggesting sustained adaptive effects of the odor of age‐matched milk.…”
Section: Discussionmentioning
confidence: 99%
“…Given the biological role of colostrum for neonates ( 8 , 162 ), its documented bioactive components as outlined here, and the potential for development as a functional food or food ingredient. There is a significant interest in developing colostrum as an ingredient to improve the bioactivity of foods and/or their potential health benefits.…”
Section: Future Directionsmentioning
confidence: 99%
“…2), and the lower cream-colored watery part at the bottom of the tube extracted and used for pouring into the mouth by using a syringe. A study by Maffei et al (28) investigated early oral colostrum administration in preterm neonates; Infants who received the oral colostrum by syringe had signi cantly higher urinary secreted immunoglobulin A and lactoferrin comparing to using a swab. Many studies have suggested early breastfeeding initiation (< 24 h), which leads to a decrease in the mortality rate in the newborn (28) (29).…”
Section: Discussionmentioning
confidence: 99%